2023
DOI: 10.1007/s11033-022-08191-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a glutamate-cysteine ligase in Bombyx mori

Abstract: Background: Glutamate cysteine ligase (GCL) is a crucial enzyme involved in the synthesis of glutathione (GSH). Despite various studies on glutathione transferase and its essential role in detoxi cation and resistance to oxidative stress, GSH synthesis has not been described in silkworms to date. Silkworms form part of the lepidopterans that are considered as a model of agricultural pests. This study aimed to understand the GSH synthesis through the GCL in silkworms so that insecticides can be formulated to ta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
0
4
1
Order By: Relevance
“…Human ChaC2 is constitutively expressed (Wang et al, 2017), whereas human ChaC1 is an inducible enzyme (Kaur et al, 2017; Mungrue et al, 2009). Previously, we found that bmGCL mRNA was highly expressed in the tissues (Afrin et al, 2023); however, here we observed that bmChaC and bmGCL mRNAs had the lowest expression levels in the silk glands on Day 3 at the fifth instar. In the tissues, bmChaC and bmGCL are involved in GSH homeostasis, which is essential for protecting tissue function.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Human ChaC2 is constitutively expressed (Wang et al, 2017), whereas human ChaC1 is an inducible enzyme (Kaur et al, 2017; Mungrue et al, 2009). Previously, we found that bmGCL mRNA was highly expressed in the tissues (Afrin et al, 2023); however, here we observed that bmChaC and bmGCL mRNAs had the lowest expression levels in the silk glands on Day 3 at the fifth instar. In the tissues, bmChaC and bmGCL are involved in GSH homeostasis, which is essential for protecting tissue function.…”
Section: Discussioncontrasting
confidence: 73%
“…We evaluated the functional characteristics of enzymes crucial for GSH homeostasis in the silkworm B. mori . We previously identified and characterized a bmGCL essential for synthesizing GSH (Afrin et al, 2023). Based on the results of a BLAST search, there is only one GGT and Dug in the silkworm genome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, yeast and bacteria have only a single Gcl gene. In insects, studies in Drosophila melanogaster revealed that DmGcl is also composed of a catalytic subunit, DmGclc, and a modifier subunit, DmGclm. , Recently, genes encoding Gclc and Gclm have been identified in Anopheles gambiae and S. litura . , However, only one Gcl gene was found in the silkworm genome . In this study, genes encoding Gclc and Gclm in FAW were cloned by RT-PCR.…”
Section: Discussionmentioning
confidence: 95%
“…23,41 However, only one Gcl gene was found in the silkworm genome. 42 In this study, genes encoding Gclc and Gclm in FAW were cloned by RT-PCR. Sequence analysis revealed that SfGclc and SfGclm contain a conserved Gcl motif and domain and share high similarity with other insect homologues.…”
Section: Discussionmentioning
confidence: 99%